La rénovation de façades vitrées à structure métallique du xxe siècle et leur préservation dans le cadre de la transition énergétique et écologique - Tanja Marzi; Lorenzo Savio (In Situ)
Metal framed glazed enclosures and curtain walls can be considered one of the most important innovations of modern architecture but are certainly a critical point in the conservation of modern heritage. Next to the most important modern architecture masterpieces, which are under special conservation and safeguard regulations, are a lot of minor and less known architectures that are part of the diffuse modern heritage and risk to be compromised in refurbishment interventions. In most cases, modern metal framed glazed façades systems do not meet the current energy requirements, and it is difficult to preserve them in their original features, finding a compromise between conservation and energy and ecological transition. This contribution presents a critical overview of the problems relating to the conservation of metal framed glazed enclosures built in the second half of the twentieth century. Requirements and standards established by energy and environmental international protocols and Italian regulations are critically analysed. Through the description of case studies, different attitudes of intervention are presented and discussed: from conservation to total replacement, with a radical change of modern building envelope original features. The mere verification of the minimum performances required by the current regulations inevitably leads to the substitution of original curtain walls. Therefore - looking beyond but respecting the regulations - architects in charge of refurbishment interventions can find innovative envelope technologies and function distribution solutions to preserve curtain walls, limiting the intervention to the strictly needed.